COMPARATIVE STUDY OF AGRONOMIC TRAITS OF DIFFERENT RICE VARIETIES GROWN UNDER SALINE AND NORMAL CONDITIONS. - Md. S. K. Khan; J. Iqbal; M. Saeed (Journal of Animal and Plant Sciences, 2014)
Salinity is a major abiotic stress limiting rice production worldwide. Identification of genotypes with better salt tolerance can promise sustained crop yields in salt affected areas. In the present research, 24 rice varieties were evaluated by conducting field trials under natural saline condition (salinity block) and normal field condition in 2010 and 2011. Pokkali, Basmati 198 and Sathra 278 were categorized as salt tolerant varieties; whereas IR36, Shaheen Basmati, Basmati 2000, Basmati 370, Basmati 6129, IR-6, KSK-133, TN-1, IRP-2 were categorized as salt susceptible varieties based on grain yield data of 2010 and 2011 field trials. Significant positive correlations of morphological traits {number of total tillers/plant, number of effective tillers/plant, panicle length, panicle weight, number of spikelets/panicle, number of grains/panicle, panicle fertility (%)} with grain yield were found under saline conditions in both years field trials. It was observed in both year field trials, under normal field conditions, days to 50% flowering and days to maturity had highly significant negative correlation with grain yield/plant, whereas under saline conditions these traits had non-significant negative correlation. During stress conditions, rice cultivars with early flowering time under normal conditions had comparative advantage under saline conditions. These cultivars had better balance between vegetative and reproductive phase, resulting in better grain yield/plant under stress conditions. Thus days to 50% flowering is an important selection criterion for salt tolerance in rice.
Keywords: Salinity; Abiotic stress; Rice production; Salt tolerance; Genotypes; Field trials; Grain yield; Morphological traits; Panicle fertility; Days to 50% flowering; Days to maturity; Selection criterion